2023
DOI: 10.1186/s42358-023-00320-4
|View full text |Cite
|
Sign up to set email alerts
|

TP53 and p21 (CDKN1A) polymorphisms and the risk of systemic lupus erythematosus

Jacyara Maria Brito Macedo,
Amanda Lima Silva,
Amanda Chaves Pinto
et al.

Abstract: Background The p53 and p21 proteins are important regulators of cell cycle and apoptosis and may contribute to autoimmune diseases, such as systemic lupus erythematosus (SLE). As genetic polymorphisms may cause changes in protein levels and functions, we investigated associations of TP53 and p21 (CDKN1A) polymorphisms (p53 72 G > C—rs1042522; p53 PIN3—rs17878362; p21 31 C > A—rs1801270; p21 70 C > T—rs1059234) with the development of systemic lupus erythematosus (SLE) in a Southeastern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that biomarkers including NEK7 [431], BMI1 [410], CAV1 [433], TRIB3 [414], SRF (serum response factor) [822], STAT1 [823], and TP53 [824] are believed to be related to the occurrence of IPF. Biomarkers including NEK7 [656], CAV1 [658], TSGA10 [665], STAT1 [825], TP53 [826], and NFKB1 [827] are reported to be associated with systemic lupus erythematosus. Biomarkers including NEK7 [686] and CAV1 [689] were associated with the risk of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that biomarkers including NEK7 [431], BMI1 [410], CAV1 [433], TRIB3 [414], SRF (serum response factor) [822], STAT1 [823], and TP53 [824] are believed to be related to the occurrence of IPF. Biomarkers including NEK7 [656], CAV1 [658], TSGA10 [665], STAT1 [825], TP53 [826], and NFKB1 [827] are reported to be associated with systemic lupus erythematosus. Biomarkers including NEK7 [686] and CAV1 [689] were associated with the risk of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that NEK7 [431], BMI1 [410], CAV1 [433], TRIB3 [414], SRF (serum response factor) [822], STAT1 [823] and TP53 [824] are an independent prognostic factors in IPF and might be associated with IPF pathogenesis. NEK7 [656], CAV1 [658], TSGA10 [665], STAT1 [825], TP53 [826] and NFKB1 [827] are associated with systemic lupus erythematosus. NEK7 [686] and CAV1 [689] were an important participant in pneumonia.…”
Section: Discussionmentioning
confidence: 99%